If sum of first m terms of AP is 2m square+3m.Then what will be its Second term?..
Attachments:
![](https://hi-static.z-dn.net/files/dd4/182d698be4d58426fcff5b2271c6c3f4.jpg)
Answers
Answered by
2
we know that,
S_n - S_(n-1) = a_n
So,
a_2 = S_2 - S_1
= {2m^2 + 3m} - {2m^2 + 3m}
= {2(2^2) + 3(2)} - {2(1^2) +3(1)}
= 8 + 6 - 2 + 3
= 14 - 5
= 9
S_n - S_(n-1) = a_n
So,
a_2 = S_2 - S_1
= {2m^2 + 3m} - {2m^2 + 3m}
= {2(2^2) + 3(2)} - {2(1^2) +3(1)}
= 8 + 6 - 2 + 3
= 14 - 5
= 9
kukki4:
difference is not same in each case?
Similar questions